Analisa Thermal Pada Permanent Magnet Sinkron Generator (PMSG) Nidec 500W - Muhammad Hifzil Alghiffari; Boni Sena; Reza Setiawan (Peneliti.net, 2022)
The generator is the main component in the wind turbine circuit, the electromagnetic induction event in the generator causes unwanted heat, the temperature generated by the coil when it is given a load is not small above 100℃, and this is at risk of damaging the components in the generator and allowing for Power Heat loss using method Finite element method. In this paper, the author aims to determine the spread of heat in the generator and the amount of heat transmitted by the coil